MANAJEMEN KULIAH KERJA LAPANGAN BERBASIS WEBSITE - Mujiono Mujiono (Cross-border, 2022)
Universities as educational institutions must be able to carry out service during the current covid-19 pandemic, with the Principles of Implementing Field Work Lectures must adapt to the needs and current conditions of society, by changing the KKL registration process system, implementing an online-based information system on the website. The researcher uses the waterfall method as a website-based software design method to build an information system for fieldwork lectures, the type of research approach applies qualitatively, the researcher collects the data sources on, Primary Data which is directly obtained from the original source and processed by the researcher directly from the subject or object researchers and interviews and secondary data derived from library information data related to program applications on the website operating system, java script programming language books, research journals that are related to this research and online data sources of internet digital documents. The presentation of data at KKL-DR uses a system with a website database in terms of data requirements, as well as system requirements for Design Tools, XAMPP software, CMS Wordpress, Macromedia DreamWeaver. Dissemination of information displayed by the institute becomes one-stop information through the KKL information system website, so IAIN Pontianak students as prospective KKL participants do not experience confusion in finding and collecting information including registration requirements as participants for Field Work Lectures.